2016
DOI: 10.30979/rev.abeno.v15i3.193
|View full text |Cite
|
Sign up to set email alerts
|

Estresse e o estilo de vida dos acadêmicos ingressantes em um curso de graduação em Odontologia

Abstract: O estresse entre os graduandos de cursos da área da saúde tem sido alvo de estudos nos últimos anos. Dentre as mudanças ocorridas no ingresso na universidade, está a adoção de um novo estilo de vida, o qual pode relacionar-se com o estado de ansiedade. O objetivo nesse estudo foi verificar a autopercepção de estresse, ansiedade e depressão dos ingressantes em um curso de graduação em odontologia, associar à resposta fisiológica do estresse e analisar seu estilo de vida. A amostra foi composta por 25 estudantes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
7
0
10
Order By: Relevance
“…In this research about stress, anxiety and depression and the academic experiences of Dental undergraduates in both study programmes, it was confirmed the presence of these elements in the life of these young college students. Stress, anxiety, and depression among freshman students were reported in several studies, the percentage of stress around 40% is considered high according to the literature 19,21,22 . Many are the causes of stress during this transitional period; however, the Personal and Interpersonal domains were more influenced in the presence of these elements; that is, students that were less adapted to the personal and interpersonal levels had a tendency to have symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this research about stress, anxiety and depression and the academic experiences of Dental undergraduates in both study programmes, it was confirmed the presence of these elements in the life of these young college students. Stress, anxiety, and depression among freshman students were reported in several studies, the percentage of stress around 40% is considered high according to the literature 19,21,22 . Many are the causes of stress during this transitional period; however, the Personal and Interpersonal domains were more influenced in the presence of these elements; that is, students that were less adapted to the personal and interpersonal levels had a tendency to have symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Many are the causes of stress during this transitional period; however, the Personal and Interpersonal domains were more influenced in the presence of these elements; that is, students that were less adapted to the personal and interpersonal levels had a tendency to have symptoms. Recent studies show how important these factors are to the student's adaptation 2,22 . Santos et al 23 tried to know the college students' opinion about the characteristics of establishing relationships with their peers and the influence of academic adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios muestran que el perfil alimentario del joven universitario sufre la influencia de los cambios que ocurren en el inicio de la vida universitaria, los cuales influyen en la adopción de nuevos patrones y hábitos alimentarios que se inician bajo la influencia de factores sociales, psicosociales y socioeconómicos, así como la propia salida de casa, que contribuye a la ruptura de algunos hábitos y a la adopción de un nuevo estilo de vida (9,10) . La influencia de esos factores observada en el presente estudio, también fue identificada en estudiantes canadienses en un estudio que describe la relación de los factores socioeconómicos con el perfil alimentario (11) .…”
Section: Discussionunclassified
“…Este factor puede estar asociado a la democratización de la enseñanza superior pública, siendo el ingreso en la vida universitaria una oportunidad para los individuos de clases sociales más bajas (12) , factor relacionado a los diferentes patrones de culturas y consecuentemente, de estilo de vida (11) . Además de este factor, otra característica encontrada en ese estudio fue el grupo etario de los estudiantes, mostrando que los jóvenes ingresan en la vida académica cada vez más temprano y pueden no asumir la responsabilidad de tener un estilo de vida saludable (9,10) .…”
Section: Discussionunclassified